Anemia and Nutritional Status of Pre-School Children in Kerala - K.A. George, N. Suresh Kumar, John J. Lal and R. Sreedevi (Indian Journal of Pediatrics, 2000; 67 (8) : 575, 2000)
A study on the pattern of anemia and its relation to nutritional status and dietary habits was conducted among 3633 pre-school children of 108 selected anganwadi centers in rural areas of Kerala State during the period 1996 to 1998. Children were invited with their parent or guardian. Capillary blood was collected from each child and hemoglobin was estimated by cyanomethemoglobin method. Weight and height of children were taken for assessing their nutritional status. The information regarding their age, sex, clinical condition and dietary habits was collected in a performa through an interview. Chi-square test was used to assess the relationship of anemia to sex, dietary habits, and nutritional status. For multivariate analysis logistic regression model was employed. The prevalence of anemia was 11.4per cent. The percentage of anemic children among male and female children was 10.25 and 12.55 respectively and statistical analysis showed that female children were more susceptible to anemia. Normal nutritional status was seen among 46.7per cent of the children. When 187 (11.78 per cent) of the mild undernourished children were anemic, the percentage anemic among the moderate undernourished children was 57 (16.37 per cent). Moderate under nutrition and anemia showed a significant association. Anemia was reported among both vegetarians and non-vegetarians. Among 927 vegetarians, 86 (9.27per cent) were anemic and among 2,706 non-vegetarians, 328 (12.1per cent) were anemic. Dietary survey revealed that, consumption of iron sources, whether haem or non-haem, was below the recommended level. Undernutrition can be attributed as the major reason for nutritional anemia. Changes in eating behaviour could have potentially affected the iron bio-availability.